Tecnologías Emergentes para la Transparencia y Ética en la Policía Nacional del Perú: Un Enfoque Innovador contra la Corrupción - Reyes Valdivia, Carlos Alberto (2025)
Corruption in the Peruvian National Police (PNP) is a structural problem that affects citizen confidence and the effectiveness of the institution. This qualitative study explores the implementation of innovative technologies, such as electric patrol cars and digital monitoring systems, to strengthen police transparency and ethics. Through the analysis of official reports, academic literature and international cases, the potential benefits of these initiatives in the reduction of police corruption are examined. The results suggest that the technologization of patrolling, together with digital oversight measures, can improve citizen perception and foster accountability within the PNP.